ChemInform Abstract: Solvent‐Free Green Synthesis of Azines and Their Conversion to 2, 5‐Disubstituted‐1, 3, 4‐thiadiazoles. Issue 17 (April 2016) - Shridevi, D. Doddramappa; Ningaiah, Srikantamurthy; Kuduva, Narayan U.; Yhya, Raad K.; Rai, Kuriya M. Lokanatha
Abstract: 1, 3, 4‐Thiadiazole derivatives (III) are synthesized via azines (II) by a solvent‐free, clean and efficient method under eco‐friendly benign reaction conditions in excellent yields.